2007
DOI: 10.1017/s0007114507831709
|View full text |Cite
|
Sign up to set email alerts
|

High-protein diets containing different milk protein fractions differently influence energy intake and adiposity in the rat

Abstract: This study was designed to determine whether (1) protein type and (2) the dietary carbohydrate to lipid content affected daily energy intake, body weight and adiposity in rats receiving high-protein diets ad libitum over a 25 d period. Each of the ten groups (n 8) consumed ad libitum one of the diets described below. A normal protein diet (P14C56L30, containing whole milk protein) and nine high-protein diets were used. The composition of the high-protein diets varied in terms of two parameters: macronutrient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 29 publications
7
35
0
Order By: Relevance
“…The effectiveness of high-protein diets in reducing adiposity shown previously in adult humans (39,50) and animals (7,9,29,42) was clearly proved for suckling piglets in the current experiment. The present obtained data further strengthen our previous observations (37) by showing that the reduction in adiposity is not limited to perirenal adipose tissue.…”
Section: Discussionsupporting
confidence: 75%
“…The effectiveness of high-protein diets in reducing adiposity shown previously in adult humans (39,50) and animals (7,9,29,42) was clearly proved for suckling piglets in the current experiment. The present obtained data further strengthen our previous observations (37) by showing that the reduction in adiposity is not limited to perirenal adipose tissue.…”
Section: Discussionsupporting
confidence: 75%
“…Veldhorst et al showed that a diet containing proteins, carbohydrates and fat providing 10, 55 and 35% energy, respectively, reduces hunger in humans if whey proteins were included in comparison to either soy and casein [10]. Similar results have been obtained from a study conducted in rats, which showed that whey protein concentrate with energy content of 55% reduced cumulative energy intake compared to whole milk protein if the former protein had been supplied in a diet with either 35% and 10% energy from carbohydrates and lipids, respectively, or in a diet with 45% energy solely from lipids [11]. No differences in cumulative energy intake were observed if the proteins were provided in diets with 15% and 30% energy from carbohydrates and fats, respectively.…”
Section: Food (Energy) Intakesupporting
confidence: 75%
“…Long-term glycomacropeptide intake has also been shown to improve fasting blood insulin levels in both humans [29] and rats [9]. Similarly a high protein diet (55% kcal) with β-lactoglobulin as it source of protein was shown by Pichon et al [11] to reduce insulin resistance and improve fasting blood insulin levels in rats to a greater extent than that of comparable high whey protein concentrate diet. The actions of α-lactalbumin and β-lactoglobulin on insulin sensitivity and glucose homeostasis may be due to the bioactive peptides in the proteins, since several dipeptides from α-lactalbumin and β-lactoglobulin have been found to increase glucose uptake in L6 myotubes and isolated skeletal muscles in vitro [39].…”
Section: Insulin Sensitivity and Glucose Homeostasismentioning
confidence: 95%
See 2 more Smart Citations